Combined interaction of PCE chains lengths, C3A and water content in cementitious systems. (16th May 2023) - Kobya, Veysel; Karakuzu, Kemal; Mardani, Ali; Felekoğlu, Burak; Ramyar, Kambiz
Graphical abstract: Highlights: The increase in C3 A content negatively affected the fresh properties. PCE with medium main and side chain lengths was the most compatible with high C3 A cement. PCE with Long side chains was the most incompatible admixture with high C3 A cement. The water content variation changed the C3 A-PCE chain interaction. Abstract: In this study, the interaction of polycarboxylate ether-based water reducing admixture (PCE) molecule chain length variation with cements having different C3 A contents and water content was investigated. For this purpose, a total of seven PCEs were synthesized following three different approaches, i.e., the main chain length changed at a constant side chain length, the side chain lengths varied at a constant main chain length, and both main and side chain lengths changed at a similar molecular weight. Paste and mortar mixtures were prepared with the PCEs and CEM I-42.5R type cements containing three different C3 A contents (3.60%, 6.82%, 9.05%). The effects of above mentioned variables on the rheological properties and compressive strength of the paste/mortar mixtures were determined. The interaction of PCEs with cements having different C3 A contents was investigated in detail by performing total organic carbon (TOC) and dynamic light scattering (DLS) analyses. The increase in the main and side chain lengths of PCE molecule up to a certain point positively affected the fresh properties of cementitious systems. Beyond a certain point (i.e. when main chain length is higher than 21 k), the increase in main chain length reduced the hydrodynamic diameter of PCE molecules (up to 32%), and decreased the dispersion performance of the admixture. The increment in side chain length (i.e. when side chain length is higher than 2100 g/mole), on the other hand, adversely affected the rheological properties, especially with high C3 A cements.